Influence of cadence and road gradient on metabolic and biomechanical parameters during submaximal cycling: A pilot 2×2 factorial study - Amatori, S.; Dell'Anna, S.; Di Noto, L.; Liberali, G.; Privitera, M.; Azzali, G.; Sisti, D.; Perroni, F.; Baldari, C.; Buzzachera, C. F. (Journal of Science and Cycling, 2024)
Introduction In cycling, a single power output can be achieved at various combinations of cadence and force; nevertheless, consensus is lacking regarding criteria for selecting the optimal cadence. Several studies reported differences in metabolic (oxygen uptake, lactate, ventilation) and neuromuscular parameters at different pedaling rates (Ahlquist et al., 1992; Lucia et al., 2001). More recently, it has also been observed that the work rates at which respiratory compensation point (RCP) and critical power (CP) occur were influenced by pedaling cadence (Broxterman et al., 2015). Furthermore, other studies indicated that joint contributions are affected by cadence, suggesting that differences in biomechanical parameters could also play a role (Skovereng et al., 2016).